(Un)disclosed. Disease disclosure in people living with rheumatic diseases: An exploratory study. (20th December 2021) - Ostuzzi, Silvia Maria Teresa; Ingegnoli, Francesca; Pistarini, Caterina; Aiello, Edoardo Nicolò; Fiabane, Elena Maria
Abstract: Objective: Little is known about disease‐related disclosure (DD) in patients with rheumatic musculoskeletal diseases (RMDs). We aim to investigate DD behaviors and to explore which socio‐demographic, clinical and psychological factors play a role in this self‐disclosure process among patients with RMDs. Methods: A cross‐sectional Italian nationwide study captured DD in RMDs in different contexts (workplace, family, friends, partner, social networks). An ad hoc survey was developed and disseminated by the Patients' Association ALOMAR ODV (Lombard Association for Rheumatic Diseases) between June and July 2020. Patient demographics, clinical data, and questionnaires assessing anxiety, depression, anticipated stigma, patient health engagement, perceived social support, and perceived general health status were collected. Results: There were 376 rheumatic patients who completed the survey. There were 73.9% of the participants who talk to others about their RMD "sometimes"; 18.7% disclose their RMD "always/very often", while 7.4% "never" talk about their RMD. A significant association was detected between DD and both perceived visibility ( P = .04) and psychological support ( P = .01). Moreover, participants who never/sometimes disclose their RMD reported significantly lower scores in the "Total" Social Support ( P < .01) and in the "Friends" subscale ( P < .001) compared to others. Psychological support and the "Friends" subscale were the only significant predictors of DD (both P = .002). Conclusions: The majority of RMD patients disclosed their disease "sometimes". The DD behavior is not associated with any specific demographic or clinical variables. Further research on the subject might help to foster better DD decision‐making processes for rheumatic patients in different contexts of daily life.